Desain Promosi Badan Pelayanan Perizinan Dan Penanaman Modal - Ari Asmawati; Anita Restuintina; Ina Shafa Marwah (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2019)
Such developments grow rapidly not only seen from the capabilities of the computer alone, one of the benefits of the development of computer technology today can we feel in the field of multimedia audio visual and broadcasting that has the role of Important in the world of information technology and functioning as a medium to fulfill, cultivate creativity and imagination into a form that is as well as desired. But for now human resources in multimedia audio visual and broadcasting has not been fulfilled.